Relationship between Death Anxiety and Happiness of Undergraduate Students of Zanjan University of Medical Sciences During the Coronavirus Disease (COVID-19) Pandemic - Bita Fathian; Mitra Payami Bousari; Farzane Ahmadi (Zanjan University of Medical Sciences and Health Services, 2023)
Background: Death anxiety is common in disease with a high mortality rate. Coronavirus disease (COVID-19) pandemic is considered a crucial factor with remarkable impact on community different age groups' mental health. Objectives: The present study aimed to determine the relationship between death anxiety and happiness during the COVID-19 pandemic among the undergraduate students of Zanjan University of Medical Sciences, Zanjan-Iran, in 2021. Methods: This correlational-descriptive study was conducted on 395 undergraduate students of Zanjan University of Medical Sciences using convenience sampling method. Data was collected through a three-part questionnaire including demographic characteristics, Templers's Death Anxiety Scale (DAS), and Oxford Happiness Inventory (OHI). For data analysis Spearman, Mann-Whitney, and Kruskal-Wallis tests were used in SPSS software version 26. Results: The results indicated that the mean (SD) scores of death anxiety and happiness were 34.04 (8.30) and 51.98 (14.43), and their median scores were 34 and 53, respectively. The death anxiety of 70.7% of the studied students was average, while the level of happiness of 40.8% of the students was average and 47.3% was high. A significant weak, inverse relationship was observed between the two variables of death anxiety and happiness (r=- 0.155, P=0.002). Conclusion: The results of the study indicated a slight decrease in happiness in students with higher death anxiety during the COVID-19 pandemic. But considering the high prevalence of death anxiety among students, especially female and non-native ones, it is necessary to pay particular attention to decreasing death anxiety in undergraduate medical students.